2021
DOI: 10.5194/hess-2020-652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Asian summer precipitation in different configurations of a high-resolution GCM at a range of decision-relevant spatial scales

Abstract: Abstract. High-resolution general circulation models (GCMs) can provide new insights into the simulated distribution of global precipitation. We evaluate how summer precipitation is represented over Asia in global simulations with a grid length of 14 km. Three simulations were performed: one with a convection parametrization, one with convection represented explicitly by the model's dynamics, and a hybrid simulation with only shallow and mid-level convection parametrized. We evaluate the mean simulated precipi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The results here are consistent with and complementary to those of Muetzelfeldt et al (2021), who analysed the same simulations and found that the summertime diurnal cycle of total precipitation over Asia was best simulated in model con gurations without parameterized convection. Furthermore, they found that the diurnal variations only improved at ner resolution in simulations without parameterized convection.…”
Section: The Diurnal Cycle Of Mcs Precipitationsupporting
confidence: 90%
See 4 more Smart Citations
“…The results here are consistent with and complementary to those of Muetzelfeldt et al (2021), who analysed the same simulations and found that the summertime diurnal cycle of total precipitation over Asia was best simulated in model con gurations without parameterized convection. Furthermore, they found that the diurnal variations only improved at ner resolution in simulations without parameterized convection.…”
Section: The Diurnal Cycle Of Mcs Precipitationsupporting
confidence: 90%
“…This has an important consequence: if the representation of MCS and its remote drivers is important (e.g., to represent extremes in rainfall), it would be desirable to use an explicit-convection simulation and a global setup. The simulations investigated in this study are promising in this regard but currently have substantial mean-state biases in Asian precipitation, thus tuning of these simulations should be a priority (Muetzelfeldt et al 2021).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations